Pelatihan Pengoperasian Microsoft Word dan Microsoft Excel Bagi Perangkat Desa dan Remaja di Desa Simpang Ketenong Kecamatan Kerkap Kabupaten Bengkulu Utara - Khairullah; Eka Sahputra; Erwadi, Yetman (JURNAL ABDIMAS SERAWAI, 2023)
Simpang Ketenong Village, Kerkap District, is classified as a self-sufficient village, with the characteristics that it has started using communication tools and technology, is not isolated and has fairly smooth traffic routes between villages and cities. (Saputera et al., 2021) Service is a process, this process produces a product in the form of a service, which is then provided to customers. Good service will also have a good impact on customers in the form of customer satisfaction, in line with findings in the field that the local village community and youth have begun to understand the importance of technology for convenience in daily work and can even support careers in the future. Along with the current development of communication technology, it has also encouraged village officials and youth in Simpang Ketenong village to be able to understand and operate computers to make work easier, both for village administration and other needs. Referring to the situation analysis above, the service team together with partners justified that the priority problems experienced by partners and the priorities agreed to be resolved were related to: the lack of skill of village officials and Simpang Ketenong Village Youth in operating computers, especially in typing and lack of understanding of how to use them. excel. Through this PKM program the team wants to contribute to providing skills to village officials and youth in the Simpang Ketenong Village area, Kerkap District, North Bengkulu Regency to be proficient in using Microsoft Word and Microsoft Excel applications. Based on the partner’s problems, the solution that will be provided in this activity is to hold Microsoft Word and Microsoft Excel Operation Training, then an evaluation will be held of village officials and local teenagers will be able to be competent in the training process that has been carried out. The targets of this Community Service are time efficiency during service, reducing data errors in reporting the performance of village officials, being able to store village databases simply, increasing knowledge for village officials and youth so that they can learn about information systems through computer media.